(untitled) (Interdisciplinary Research in Education, 2021)
This paper presents a model for the perception of students relating the ICT integrated pedagogy into practice. The objective of this paper is to analyze the perception of students towards the practice of ICT integrated pedagogy in diverse Mathematics classes. Eighty Mathematics students who were selected randomly from the Department of Mathematics Education, TU, Kathmandu, were the participants. The opinionnaire form was used as a major tool. As the design was quantitative, data was analyzed using percentile, weighted mean, and chi-square test. The findings of the study revealed that there is a positive perception of students on the implementation, process and output of ICT integrated pedagogy. The students reflected that ICT integrated pedagogy has a positive impact to improve their achievement in mathematics. The perception of students shows there is a pedagogical shift from the conventional teaching approach to ICT integrated pedagogy. However, teachers try to use ICT integrated pedagogy in the classroom but some of them have little knowledge and misconception about the use of ICT integrated pedagogy regarding time and resource constraints to practice itin Mathematics classes.